RBP4 activates antigen-presenting cells leading to adipose tissue inflammation and systemic insulin resistance - Moraes-Vieira, Pedro M. (2014)
Insulin resistance is a major cause of diabetes and is highly associated with adipose tissue (AT) inflammation in obesity. RBP4, a retinol-transporter, is elevated in insulin resistance and contributes to increased diabetes risk. We aimed to determine the mechanisms for RBP4-induced insulin resistance. Here we show that RBP4 elevation causes AT inflammation by activating innate immunity which elicits an adaptive immune-response. RBP4-overexpressing mice (RBP4-Ox) are insulin-resistant and glucose-intolerant and have increased AT macrophage and CD4 T-cell infiltration. In RBP4-Ox, AT CD206(+) macrophages express pro-inflammatory markers and activate CD4 T-cells while maintaining alternatively-activated macrophage markers. These effects result from direct activation of AT antigen-presenting cells (APCs) by RBP4 through a JNK-dependent pathway. Transfer of RBP4-activated APCs into normal mice is sufficient to induce AT inflammation, insulin resistance and glucose intolerance. Thus, RBP4 causes insulin resistance, at least partly, by activating AT APCs which induce CD4 T-cell Th1 polarization and AT inflammation.